(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
As an apropos of a program held in Leuven, Belgium, has been suggested to build a watercraft that can be controlled from the riverbank. The show was a big belgian program, the celebration of the canonization of Father Damien. Father Damien was a roman catholic priest at the 19th century. He won recognition for his ministry to people with leprosy (also known as Hansen’s disease), who had been placed under a government-sanctioned medical quarantine on the island of Molokai in the Kingdom of Hawaii.